Haplotype Analysis Sheds Light on the Genetic Evolution of the Powdery Mildew Resistance Locus Pm60 in Triticum Species - Xuhui Huang; Xueli Jin; Xiaojie Ren; Wenxuan Wu; Wenjun Ji; Lihua Feng; Bo Jiang; Ming Hao; Shunzong Ning; Zhongwei Yuan; Lianquan Zhang; Bihua Wu; et al. (Pathogens, 2023)
Wheat powdery mildew (Blumeria graminis f. sp. tritici, Bgt, recently clarified as B. graminis s. str.), is one of the most destructive diseases of wheat. Pm60 is a nucleotide-binding leucine-rich repeat (NLR) gene that confers race-specific resistance to Bgt. Allelic variants (Pm60, Pm60a, and Pm60b) were found in Triticum urartu and T. dicoccoides, the wild progenitors of wheat. In the present study, we studied the diversity of the Pm60 locus in a large set of wheat germplasm and found 20 tetraploid wheats harboring the Pm60 alleles, which correspond to three novel haplotypes (HapI–HapIII). HapI (Pm60 allele) and HapII (Pm60a allele) were present in domesticated tetraploid wheats, whereas HapIII (Pm60a allele) was identified in wild tetraploid T. araraticum. A sequence comparison of HapII and HapIII revealed that they differed by three SNPs and a GCC deletion. Results of the phylogenetic analysis revealed that HapII was more closely related to the functional haplotype MlIW172. Infection tests showed that HapII-carrying lines display a partial resistance response to Bgt#GH, while HapI was susceptible. Our results provide insights into the genetic evolution of the Pm60 locus and potential valuable alleles for powdery mildew resistance breeding.